ANALYSIS OF STUDENTS' MATHEMATICAL COMMUNICATION BASED ON SYSTEMATIC AND INTUITIVE COGNITIVE STYLE - Trihara, Putri Ayu; Shodiqin, Ali; Pramasdyahsari, Agnita Siska (Math Educa Journal, 2024)
Through communication, students can explore and strengthen mathematical thinking and knowledge and develop the ability to solve problems using mathematical language, thus forming mathematical communication. This research aims to analyze students' mathematical communication based on systematic and intuitive cognitive styles in the SPLTV (Systems of Linear Equations in Three Variables) material in class X at Nurul Muslim High School. This research adopts a descriptive qualitative approach. The subjects of this research were 2 students with a systematic cognitive style and 2 students with a cognitive style as determined from the CSI (Cognitive Style Inventory) test. Research subjects were given a test, then a test-based interview was conducted to dig up further information. Data analysis was carried out by reduction, presentation and drawing conclusions. Source triangulation is used to check the validity of the data. The results of this research show that students with a systematic cognitive style can fulfill all indicators of mathematical communication. Characterized by being able to write complete information, create mathematical models, solve problems, and make appropriate conclusions. Students with a intuitive cognitive style are not yet able to fulfill all indicators of mathematical communication. Characterized by difficulty writing complete information. Able to create mathematical models, but unable to finalize the final results or draw conclusions due to errors in finding variables.